Efficient preparations of fluorine compounds - Roesky, H. W. (Wiley, 2013)
"This book brings together contributions written by leading researchers and covering a wide scope of fluorine chemistry. It is a comprehensive listing of methods for synthesizing fluorine compounds for a wide variety of compounds whereby the C-H bond is replaced by a C-F bond"--